2012
DOI: 10.2165/11633750-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Use, the Prevalence of Bridging, and Relation to Length of Stay among Hospitalized Patients with Non-Valvular Atrial Fibrillation

Abstract: Objective: The objectives of this study were to describe inpatient anticoagulation and bridging in patients with non-valvular atrial fibrillation (NVAF) and to identify whether differences exist in length of stay (LOS) among bridged versus non-bridged NVAF patients. Design: Administrative claims data were used to select patients ‡18 years with a primary or secondary discharge diagnosis of NVAF and inpatient warfarin use from 1 July 2004 to 30 September 2009. Patients with valvular or transient causes of NVAF o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…First, recommendations in guidelines9, 10, 12 and summaries of product characteristics14, 15 do not strongly advise against bridging therapy. Indeed, several health professionals have criticized the lack of clarity of these guidelines 17, 18, 19, 42, 43…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, recommendations in guidelines9, 10, 12 and summaries of product characteristics14, 15 do not strongly advise against bridging therapy. Indeed, several health professionals have criticized the lack of clarity of these guidelines 17, 18, 19, 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation in guidelines9, 10, 12 and summaries of product characteristics14, 15 is less clear for those with stable NVAF who do not require rapid anticoagulation. In real‐life conditions, a bridging regimen is commonly used in those with a low stroke risk 16, 17, 18, 19. This practice is not supported by evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of SmoyerTomic et al [5]. also indicated that LMWH (63.1%) was the most commonly used agent, followed by UFH (54.6%), bivalirudin (1.2%), fondaparinux (0.8%), and argatroban (0.1%).…”
mentioning
confidence: 90%
“…Just as Smoyer-Tomic et al [5]. note in their limitations, their study fails to ascertain the reason for bridging therapy and longer LOS amongst bridging than amongst nonbridging patients.…”
mentioning
confidence: 90%
See 1 more Smart Citation